Pesona Indonesia Pariwisata,Budaya,dan Sosial lebih dekat mengenal Pulau Sulawesi - Satrio A.Y. (PT Bintang Ilmu, 2009)
Pesona Indonesia Pariwisata,Budaya,dan Sosial lebih dekat mengenal Pulau Sulawesi